Interactive Learning Multimedia with Problem-Based Learning for Fifth-Grade Elementary School Students - Arnindya Navitri Ainullah; I Nyoman Jampel; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2023)
There are limitations and a need for teacher ability to utilize technology to create innovative supporting teaching materials for students. The purpose of this research is to develop interactive learning multimedia. This type of research is development research with the ADDIE model. The subjects involved in this study were content experts, design experts, media experts, and trial students. Data were collected using the questionnaire and test methods, with assessment instruments in the form of learning achievement tests and test sheets for the validity of media products. The data obtained in the study were then analyzed using qualitative descriptive analysis techniques, quantitative descriptive, and t-test inferential statistical analysis. The results of this development research show that the design and development of interactive learning multimedia include five stages of the ADDIE model, product validity obtained from the review results of very well-qualified content experts (93.33%), very well-qualified design experts (93.75%), qualified media experts very good (93.33%), the results of the individual trials were very well qualified (93.66%), and the small group trials were very well qualified (92.56%), the results of the multimedia effectiveness test obtained an average pretest of 51.57 and an average of posttest 87.85. It was concluded that problem-based learning-based interactive multimedia is very qualified and feasible to implement and use in the Indonesian content learning process.